2021
DOI: 10.3389/fbioe.2021.702173
|View full text |Cite
|
Sign up to set email alerts
|

Lentinan-Based Oral Nanoparticle Loaded Budesonide With Macrophage-Targeting Ability for Treatment of Ulcerative Colitis

Abstract: Ulcerative colitis (UC) is a global, chronic, and refractory disease. Corticosteroids are first-line drugs for the treatment of UC but also cause adverse side effects. Budesonide (BUD), a corticosteroid with relatively low side effects, has been approved by the Food and Drug Administration for use as enteric capsules (Entocort EC) for the treatment of inflammatory bowel disease (IBD). However, this formulation lacks specific targeting ability to UC lesions. Herein, we describe the development of an advanced ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Lentinan had a potential anti-inflammatory effect on LPS-induced intestinal inflammatory response of juvenile taimen (Hucho taimen, Pallas) 20 . Emerging data have demonstrated that lentinan-based oral nanoparticle-loaded Budesonide (NT/BUD-NPs) significantly alleviated Ulcerative Colitis by targeting ability for treatment 21 . Moreover, lentinan significantly improved gut microbiota dysbiosis by decreasing phylum Proteobacteria and Epsilonbacteraeota 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Lentinan had a potential anti-inflammatory effect on LPS-induced intestinal inflammatory response of juvenile taimen (Hucho taimen, Pallas) 20 . Emerging data have demonstrated that lentinan-based oral nanoparticle-loaded Budesonide (NT/BUD-NPs) significantly alleviated Ulcerative Colitis by targeting ability for treatment 21 . Moreover, lentinan significantly improved gut microbiota dysbiosis by decreasing phylum Proteobacteria and Epsilonbacteraeota 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis (UC) is also called chronic nonspecific ulcerative colitis. 1 It is one of the two main forms of inflammatory bowel disease (IBD) 2 that typically occurs in the rectum and proceeds proximately, even involving the mucosa in a symmetric uninterrupted pattern. 3 UC patients commonly exhibit weight loss, abdominal pain, and bloody diarrhoea, which severely reduce the quality of life of the individual and even lead to death.…”
Section: Introductionmentioning
confidence: 99%
“…Other natural polymers that have attracted research interest for delivery purposes include, but are not limited to, glycogen [114][115][116], starch [114,[117][118][119][120], lignin [121,122], heparin [123,124], lentinan [14,125,126], and chondroitin sulfate [127][128][129].…”
Section: Other Natural Polymersmentioning
confidence: 99%